Đánh giá tốc độ phản ứng oxi hóa amoni trong kỹ thuật màng sinh học tầng chuyển động - Cát, Lê Văn; Trang, Nguyễn Thị Thu (Vietnam Journal of Chemistry, 2012)
Nitrification presents a slow process in water and wastewater treatment. Several reaction techniques are being applied, such as moving bed biofilm reactor (MBBR), to promote the nitrification rate. The nitrification kinetics of the system is complex involving bioprocesses and transport within the media, but the design and operation of a treatment system  require kinetic data. For the pragmatic purpose, the kinetic data of the nitrification process performed  in MBBR was analysed by the formal chemical reaction  to obtain the reaction constant and reaction order  under completely mixed flow conditions. The dependences of reaction rate, reaction order as well as reaction constant upon the influent ammonia concentration were presented and discussed by means of transport qualitatively.